Therapeutic Hypothermia in Stroke and Traumatic Brain Injury - Faridar, Alireza; Bershad, Eric M.; Emiru, Tenbit; Iaizzo, Paul A.; Suarez, Jose I.; Divani, Afshin A. (Frontiers in Neurology, 2011)
Therapeutic hypothermia (TH) is considered to improve survival with favorable neurological outcome in the case of global cerebral ischemia after cardiac arrest and perinatal asphyxia. The efficacy of hypothermia in acute ischemic stroke (AIS) and traumatic brain injury (TBI), however, is not well studied. Induction of TH typically requires a multimodal approach, including the use of both pharmacological agents and physical techniques. To date, clinical outcomes for patients with either AIS or TBI who received TH have yielded conflicting results; thus, no adequate therapeutic consensus has been reached. Nevertheless, it seems that by determining optimal TH parameters and also appropriate applications, cooling therapy still has the potential to become a valuable neuroprotective intervention. Among the various methods for hypothermia induction, intravascular cooling (IVC) may have the most promise in the awake patient in terms of clinical outcomes. Currently, the IVC method has the capability of more rapid target temperature attainment and more precise control of temperature. However, this technique requires expertise in endovascular surgery that can preclude its application in the field and/or in most emergency settings. It is very likely that combining neuroprotective strategies will yield better outcomes than utilizing a single approach.